2022
DOI: 10.3390/bs12090308
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gender on STEAM Education in Elementary School: From Individuals to Group Compositions

Abstract: Gender differences are essential factors influencing collaborative learning at both individual and group levels. However, few studies have systematically investigated their impact on student performance in the innovative context of STEAM education, particularly in the elementary school setting. To address this research need, this study examined the learning behaviors of 91 sixth graders in a STEAM program, who were classified into three gender groupings, namely, boy-only, girl-only, and mixed-gender groups, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
1
1
Order By: Relevance
“…However, students in mixed-gender groups had the fewest conversations and demonstrated more irrelevant behaviors. This contradicts the previous findings in Jiang et al [ 14 ] and Ma et al [ 9 ], who reported that mixed-gender groups had a more relaxed atmosphere and more conversations occurred. One possible reason for their findings is that the participants of these studies were elementary school students (fourth- and sixth-grade students, respectively), who are more expressive of their emotions and viewpoints when confronted with opposite-gender group members.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, students in mixed-gender groups had the fewest conversations and demonstrated more irrelevant behaviors. This contradicts the previous findings in Jiang et al [ 14 ] and Ma et al [ 9 ], who reported that mixed-gender groups had a more relaxed atmosphere and more conversations occurred. One possible reason for their findings is that the participants of these studies were elementary school students (fourth- and sixth-grade students, respectively), who are more expressive of their emotions and viewpoints when confronted with opposite-gender group members.…”
Section: Discussioncontrasting
confidence: 99%
“…Collaborative learning, as a social-constructive instructional strategy, has become increasingly popular in higher education to promote students’ learning engagement [ 1 , 2 ], social interaction [ 3 , 4 ], and academic performance [ 5 , 6 ]. The key to excellent group performance and individual gains in collaborative learning is the quality of interpersonal interaction among participants [ 7 ], which is influenced by group composition [ 8 , 9 ]. Gender, as a key demographic attribute, has been regularly used to compose collaborative learning groups [ [10] , [11] , [12] , [13] ], and gender diversity induced a wide range of factors highly relevant for group functioning, such as behavioral patterns [ 14 ], peer interaction [ 15 ], and emotional expression [ 16 , 17 ], which determine the overall efficacy and experience of collaborative learning.…”
Section: Introductionmentioning
confidence: 99%
“…Sementara pada afiliasi Johannes Kepler University cenderung meneliti terkait visualisasi, dan modelling pembelajaran matematik menggunakan masalah nyata dengan menggunakan STEAM (Haas et al, 2023;Ortiz-Laso et al, 2023). Di kawasan China, yakni pada Central China Normal University banyak meneliti terkait implementasi, dan pengaruh dari implementasi STEAM terkait kolaborasi, motivasi, dan self-efficacy (Jia et al, 2021;Ma et al, 2022). Temuan ini tentu menjadi hal yang menarik, karena pada umumnya penelitian analisis bibliometrik hanya menjelaskan terkait afiliasi-afiliasi populer apa saja yang menerbitkan terkait STEAM (Phuong et al, 2023), tanpa menjelaskan dengan detail kecenderungan penelitian yang dilakukan terkait STEAM.…”
Section: Gambar 5 Jumlah Artikel Afiliasi Terkait Steam Yang Ditulis ...unclassified
“…Even today, interdisciplinary education still exudes the charm of life for engineering education [2]. In creating different contexts, interdisciplinary education can improve the learning effectiveness and engineering literacy of engineering college students [3].If we can learn effective STEAM education concept, and the integration of national conditions of education environment, promote interdisciplinary, the integration of science and society, thus can really achieve training professional applied, the goal of talent [4]. At present, despise engineering education in higher vocational colleges, by learning from STEAM education concept can make students in the solid basic knowledge at the same time break the barriers between disciplines, improve vocational students engineering thinking, for the development of the society to cultivate more applied talents, to meet the challenge of the future society [5].…”
Section: Introductionmentioning
confidence: 99%